FACTORS AFFECTING THE KEI COMMUNITY IN THE SELECTION OF CONTRACEPTION IN SOUTHEAST MALUKU - Viona Intan Safitri; Ashon Sa'adi (Universitas Airlangga, 2022)
Abstract Background: The Kei tribe are indigenous people from Southeast Maluku Regency. Culture in society affects people's attitudes when deciding to use contraception. This study aims to determine the factors that influence the Kei ethnic community in choosing contraception in the work area of ​​the Ibra Health Center, Southeast Maluku Regency. Method: This study uses primary data from 227 couples of childbearing age (EFA) whose husbands are from the Kei tribe. The results of this study indicate that a p-value of 0.000 was obtained based on the results of the chi-square statistical test between the variables of knowledge and use of contraceptives. The value of < 0.05 for the relationship between knowledge and contraceptive use. Chi-squere statistical test was performed to obtain a p-value of 0.000. The value of < 0.05 so that there is a relationship between the number of children and the use of contraception. Result: There is a relationship between culture and the use of contraceptives by performing a chi square statistic test to obtain a p-value of 0.000. The value of < 0.05 . based on the chi square test, there is a relationship between husband's support and contraceptive use with a p value of 0.000. Conclusion: of this study is that there is a relationship between family planning knowledge and the choice of contraception, culture with the choice of contraception, husband's support with the choice of contraception and the relationship between the number of children and the choice of contraception. Keywords: Knowledge, Culture, Husband's Support, Number of Children